"PANCHAKARMA IN PEDIATRIC CARE: NURTURING INFANT HEALTH AND DEVELOPMENT" (International Journal of Food and Nutritional Sciences, 2022)
Panchakarma, a corners Panchakarma, an integral component of Ayurvedic medicine, comprises five therapeutic procedures—Vamana (emesis), Virechana (purgation), Basti (enema), Nasya (nasal administration), and Raktamokshana (bloodletting)—aimed at detoxifying the body and restoring its balance. While extensively studied in adults, the application of Panchakarma in infants is garnering increased attention and research due to its potential to promote holistic health from an early age. This review delves into the adaptation of Panchakarma for pediatric care, highlighting its principles, procedures, and benefits. In infants, the predominance of the Kapha dosha, essential for growth and development, necessitates a careful and modified approach to these treatments. Adapted techniques such as gentle Swedana (sudation therapy), Abhyanga (oil massage), mild Shirodhara (oil pouring on the forehead), adjusted Basti (herbal enemas), and Nasya (nasal drops) are discussed. The potential benefits include enhanced immunity, improved digestion, balanced growth, stress reduction, and effective detoxification.